A systematic review of counterfeit and substandard medicines. (24th May 2012) - Almuzaini, T; Choonara, I; Sammons, H
Abstract : Aim: To explore the prevalence and global health implications of counterfeit (fraudulently) and substandard (failed to pass quality measurements) medicines. Methods: A systematic review was conducted using Embase, Medline, PubMed and International Pharmaceutical Abstracts, including articles published till May 2011. Only prevalence studies containing original data were included. Data was collected on prevalence of these drugs, year of the study, location, drugs involved, sample size, paediatric formulations and drug concentrations of counterfeit/substandard medicines. Results: Forty-two prevalence studies were identified. The overall median prevalence of counterfeit and substandard medicines reported was 36%. These studies were conducted in thirty-eight different countries; the majority (34 studies) were focussed on low-income countries (LIC) and lower-middle-income countries (LMIC), the remainder having mixed groups. The median prevalence in the samples was similar in LIC and LMIC in Africa and Asia (35% to 38%). No individual data about the prevalence in upper-middle-income countries (UMIC) and high-income countries (HIC) was available. Antimicrobial drugs were the most extensively studied group of medicines (34 studies); antimalarials were the focus in two thirds (22 studies). Seven studies compared the failure rate in authorised and unauthorised suppliers, the percentage of failed samples was significantly higher in the unauthorised suppliers (41.2% versus 23.4%; p= 0.0001). Studies showed inadequate amount of active ingredients (83%), absence of active ingredients (15%) and excessive amount of active ingredients (15%). Only eleven studies included paediatric formulations (i.e. syrup and suspension) in their sampling process and one third (113) of the 338 samples tested were substandard. Conclusion: There is a widespread use of counterfeit and substandard medicines throughout Africa and Asia in LIC and LMIC. More than a third of medicines available in these countries could be counterfeit or substandard. The extent of the problem in UMIC and HIC is not certain. There is limited evidence on paediatric formulations and children would be at higher risk from dose changes. The use of poor quality medicines can lead to a lack of efficacy, therapeutic failure, toxicity, and the emergence of drug resistance. Public education, legislations and strong law enforcement are needed to curb this trade.